The Serâbît Inscriptions - Bruston, Charles (Harvard theological review, 1929)
Shortly after the publication of my study on the Inscription of Solomon I learned of the new Canaanite inscriptions recently brought from Sinai by Professors Lake and Blake and published by them and Professor Butin in the Harvard Theological Review for January, 1928. Having attempted several years ago, in the Revue Archeologique (1921 and 1922), to explain the earlier ones, I naturally wished to see if I might not read these also and get at their meaning. In this I think I have succeeded, at least to a moderate degree. The first steps in deciphering the ten or twelve documents discovered at Serâbît, near Sinai, were taken by the English scholars A. H. Gardiner and A. Cowley. The former identified the name of Bahalath, the latter that of Tanit, as well as the pronoun ןא (Hebrew ינא ‘I’) and especially the expression םענ לע, which means ‘because of favor.’ Several other words, including ןכ ‘son,’ ןתנ ‘give,’ were recognized within a short time, so that a goodly number of the twenty-two letters of the alphabet were thus identified.